Trefoil factor 3 (TFF3) is involved in cell migration for skeletal repair - Krüger, Katharina; Schmidt, Sebastian; Paulsen, Friedrich; Ignatius, Anita; Klinger, Patricia; Hotfiel, Thilo; Swoboda, Bernd; Gelse, Kolja (International Journal of Molecular Sciences, 2019)
The aim of the study was to explore the possible role of Trefoil Factor Family peptide 3 (TFF3) for skeletal repair. The expression of TFF3 was analyzed in human joint tissues as well as in a murine bone fracture model. Serum levels of TFF3 following a defined skeletal trauma in humans were determined by ELISA. The mRNA expression of TFF3 was analyzed under normoxia and hypoxia. Expression analysis after stimulation of human mesenchymal progenitor cells (MPCs) with TFF3 was performed by RT2 Profiler PCR Array. The effect of recombinant human (rh)TFF3 on MPCs was analysed by different migration and chemotaxis assays. The effect on cell motility was also visualized by fluorescence staining of F-Actin. TFF3 was absent in human articular cartilage, but strongly expressed in the subchondral bone and periosteum of adult joints. Strong TFF3 immunoreactivity was also detected in murine fracture callus. Serum levels of TFF3 were significantly increased after skeletal trauma in humans. Expression analysis demonstrated that rhTFF3 significantly decreased mRNA of ROCK1. Wound healing assays showed increased cell migration of MPCs by rhTFF3. The F-Actin cytoskeleton was markedly influenced by rhTFF3. Cell proliferation was not increased by rhTFF3. The data demonstrate elevated expression of TFF3 after skeletal trauma. The stimulatory effects on cell motility and migration of MPCs suggest a role of TFF3 in skeletal repair.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Cell migration; Chemotaxis; Fracture healing; Mesenchymal progenitor cells; TFF3